Knowledge of care providers on the management of high blood pressure in the Boma health zone, Democratic Republic of Congo, 2024 - Romain Mvemba; Bernard-Kennedy Nkongolo; Steve Botomba; Marie-Claire Muyer (Journal of Global Health Economics and Policy)
# Background High blood pressure, also known as hypertension, is a major public health issue globally, affecting approximately 1.13 billion people worldwide. It is a leading risk factor for cardiovascular diseases, which are responsible for a significant number of deaths annually. In the Democratic Republic of the Congo (DRC), the prevalence of hypertension is alarmingly high, with various studies indicating that a substantial portion of the adult population is affected. Effective management of hypertension requires comprehensive knowledge of the disease among healthcare providers. This study explores the knowledge of providers on the management of high blood pressure in the Boma Health Zone in 2024.